2012
DOI: 10.1007/s00018-012-1211-2
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship between bone and fat: from cellular see-saw to endocrine reciprocity

Abstract: The number of mature osteoblasts and marrow adipocytes in bone is influenced by the differentiation of the common mesenchymal progenitor cell towards one phenotype and away from the other. Consequently, factors which promote adipogenesis not only lead to fatty marrow but also inhibit osteoblastogenesis, resulting in decreased osteoblast numbers, diminished bone formation and, potentially, inadequate bone mass and osteoporosis. In addition to osteoblast and bone adipocyte numbers being influenced by this skewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 246 publications
2
70
0
12
Order By: Relevance
“…However, clinical investigation demonstrated a positive link between serum leptin levels and bone mineral density (BMD), especially in women. Yet a number of other studies suggested no correlation [114]. Adiponectin is another adipose secreted adipokine with critical roles in glucose metabolism and energy homeostasis [115].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…However, clinical investigation demonstrated a positive link between serum leptin levels and bone mineral density (BMD), especially in women. Yet a number of other studies suggested no correlation [114]. Adiponectin is another adipose secreted adipokine with critical roles in glucose metabolism and energy homeostasis [115].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…Freidenstein [ 33 ] coined the terms inducible and determined osteoprogenitor cells (IOPCs and DOPCs) to indicate that there were stromal that were pluripotential and could be induced to form osteoblasts, while other cells further along the differentiation pathway were irreversibly differentiated. This concept was revised because cells that have many of the characteristics of DOPCs can be diverted in culture to other phenotypes such as adipocytes or cartilage cells [ 34 ]. Thus it seems more likely that the process of differentiation is a continuum with many different stages.…”
Section: Osteoblasts and Osteocytesmentioning
confidence: 98%
“…Studies conducted in the last several years indicate that bone marrow adipocytes have the characteristic features of subcutaneous and visceral fat [1,14]. They are metabolically active as they secrete multiple biologically active substances that affect osteoblastogenesis.…”
Section: Metabolic Activity Of Adipose Tissue and Osteogenesismentioning
confidence: 99%
“…Thus, what we encounter here is a positive feedback loop: a signal sent by the pancreas via an osteoblast promotes osteocalcin secretion, which in turn stimulates beta cells to produce insulin. One may presume that the process is to compensate energy expenditure related to osteogenesis, and the term "bone-pancreas axis" has been coined as a result [14,48]. The bond of negative regulation that is necessary in every biological process turns out to be leptin.…”
Section: Bone and Energy Balancementioning
confidence: 99%